Redefining Onyx HD 500 in the Flow Diversion Era - Richard Tyler Dalyai; Ciro Randazzo; George Ghobrial; L. Fernando Gonzalez; Stavropoula I. Tjoumakaris; Aaron S. Dumont; Robert H. Rosenwasser; Pascal Jabbour (International Journal of Vascular Medicine)
We report the largest US case series results using Onyx HD-500 (EV3), a new liquid embolic agent, in the successful treatment of 21 patients with wide-neck intracranial aneurysms (mean size 4.5 mm), which are at increased risk of incomplete occlusion or recanalization with standard endovascular intervention utilizing detachable platinum coils. All aneurysms were located in the anterior circulation, and three aneurysms presented as acute subarachnoid hemorrhages. Complete aneurysm occlusion was present in 19 of 21 patients (90%). On six-month followup, one patient with an initially small residual neck progressed to total occlusion. Aneurysm recanalization was not detected in any patients on mean follow up of 8.9 months in 11 patients. Four patients experienced transient neurologic deficits in the immediate postoperative period and one in a delayed fashion. Embolization with the liquid embolic agent Onyx appears to be a safe and effective endovascular modality of treatment for wide-neck aneurysms or recurrent aneurysms that had previously failed treatment with detachable coils.